Applying unsupervised machine learning models to identify serve performance related indicators in women`s volleyball - Casimiro-Artés, M. Á.; Hileno, R.; Garcia-de-Alcaraz, A. (Research Quarterly for Exercise and Sport, 2024)
In volleyball, the effect of different factors on serve performance has usually been analyzed with traditional statistical techniques such as logistic regression or discriminant analysis.